Strategi Pemasaran Digital Dalam Peningkatan Penerimaan Mahasiswa Baru Menggunakan Analisis SWOT - Kristanto, Titus; Hadiansyah, Walid Maulana; Nasrullah, Muhammad; Amalia, Amanda; Anggraini, Erlin Yuli; Firmansyah, Ainurrohman (MULTINETICS, 2020)
One of the tertiary institutions in Surabaya City, East Java Province, is experiencing a decline in new students from the target that has been determined in previous years. The analysis conducted by tertiary institutions uses a SWOT analysis approach, by looking at the conditions experienced both from internal and external aspects. In addition, tertiary institutions also look at the aspects of opportunities and threats that affect new student admissions. In addition to looking at the four aspects, universities see the supporting factor in the admission of new students from the variable "Quality of higher education that can give an attractive impression", because this variable is very influential on new student admissions. This makes universities carry out digital marketing strategies. The target of new student candidates is students who have potential. Digital marketing media is the use of social media (Facebook and Instagram) and advertising on local television and local radio. The result of digital marketing is that it can increase the admission of new students, thereby increasing the reputation of higher education institutions and optimizing digital marketing.